A longitudinal cohort study of the relationship between Thimerosal-containing hepatitis B vaccination and specific delays in development in the United States: Assessment of attributable risk and lifetime care costs. Issue 2 (June 2016) - Geier, David A.; Kern, Janet K.; Hooker, Brian S.; King, Paul G.; Sykes, Lisa K.; Geier, Mark R.
Abstract: Epidemiological evidence suggests a link between mercury (Hg) exposure from Thimerosal-containing vaccines and specific delays in development. A hypothesis-testing longitudinal cohort study ( n  = 49, 835) using medical records in the Vaccine Safety Datalink (VSD) was undertaken to evaluate the relationship between exposure to Hg from Thimerosal-containing hepatitis B vaccines (T-HBVs) administered at specific intervals in the first 6 months of life and specific delays in development [International Classification of Disease, 9th revision (ICD-9): 315.xx] among children born between 1991 and 1994 and continuously enrolled from birth for at least 5.81 years. Infants receiving increased Hg doses from T-HBVs administered within the first month, the first 2 months, and the first 6 months of life were significantly more likely to be diagnosed with specific delays in development than infants receiving no Hg doses from T-HBVs. During the decade in which T-HBVs were routinely recommended and administered to US infants (1991–2001), an estimated 0.5–1 million additional US children were diagnosed with specific delays in development as a consequence of 25 μg or 37.5 μg organic Hg from T-HBVs administered within the first 6 months of life. The resulting lifetime costs to the United States may exceed $1 trillion.